The Influence Of Service Quality And Product Quality To Customers Satisfaction And Their Effects To Customers Loyalty On The Customers Of Waroeng Ngangeni, Andaru Jaya Makmur Company - Tresiani, Yunita Dwi; Farradia, Yuary; Hannan, Sufrin (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This study aimed investigate to know that influence of service quality and product quality on customers satisfaction in shaping customers loyalty of Rumah Makan Waroeng Ngangeni. By using proporsioal sampling, there are 40 total samples who are the consumers of Rumah Makan Waroeng Ngangeni. Descriptive analysis and path analysis are used as data analysis techniques. The data are collected through questionnaire. The result of this research shows that: service quality has significant effects on customers satisfaction; product quality has significant effects on customers satisfaction, service quality has significant effects on customers loyalty; product quality has significant effects on customers loyalty; customers satisfaction has significant effects on customers loyalty; service quality has significant effects on customers loyalty through customers satisfaction; and product quality has significant effects on customers loyalty through customers satisfaction. Thus, Rumah Makan Waroeng Ngangeni had better to continue to improve their service quality and product quality. So that, it will influence Customers Satisfaction and customers will continue to become loyal.